Self-Resilience in Children After Losing a Father Due to Covid-19 (Case Study in Cempaka Putih Village, East Ciputat District, South Tangerang City) - Faradibba Maiwa Radika Nur Ramadhan; Moh. Amin Tohari; Ati Kusmawati; Muhammad Sahrul (Budapest International Research and Critics University, 2023)
This research is entitled Self Resilience in Children After Losing a Father Due to Covid-19 (Case Study in Cempaka Putih Village, East Ciputat District, South Tangerang City). Covid-19 is a non-natural disaster that impacts the death of loved ones, including parents. Losing someone significant in life forever has a big impact on the survival of the person left behind, especially for a child who has lost a father figure in his life due to Covid-19. This condition will cause the child to become stressed, sad, grieving, shocked, and emotionally uncontrollable. This requires the child to be able to rise, which is called Resilience. This study aims to determine self-resilience in children after the loss of a father due to Covid-19. The Grand Theory used is Resilience Theory. This study uses a qualitative approach with a descriptive method. The informants of this study consisted of 8 people who were divided into key informants (4 people) and supporting informants (4 people), using the Purposive Sampling Technique, with data analysis using Source Triangulation. The study's results showed that the child's condition after the loss of a father due to Covid-19 experienced sadness, grief, surprise, confusion, irritability, uncontrolled emotionality, and decreased achievement at school. With this happening, the Resilience that is built in children goes through seven components of Resilience, namely Emotion Regulation (ability to be calm and focus on problem-solving), Impulse Control (ability to control emotional attitudes in various ways), Optimism (having the confidence to be able to rise). Empathy (getting different support from others), Causal Analysis (being able to understand the causes of problems that occur), Self-Efficacy (having a commitment to rise from problems through various ways that he believes in), and Reaching Out (able to take the positive side of the problem that happened).